2021
DOI: 10.1039/d0qm00719f
|View full text |Cite
|
Sign up to set email alerts
|

Developing D–π–D hole-transport materials for perovskite solar cells: the effect of the π-bridge on device performance

Abstract: Three cost-effective D-π-D hole transport materials (HTMs) with different π-bridge including biphenyl (SY1), phenanthrene (SY2) and pyrene (SY3) have been synthesized by one-pot reaction with cheap commercially available starting materials...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In order to address this shortcoming, solid-state hole-transporting material (HTM) 2,2′,7,7′-tetrakis­( N , N -di- p -methoxyphenyl-amine)-9,9′-spirobifluorene (Spiro-OMeTAD) was employed as an alternative to liquid electrolyte to successfully construct the first all solid-state mesoscopic heterojunction PSCs featuring a FTO/c-TiO 2 /m-TiO 2 /perovskite/HTM/Au cell configuration that was stable for 500 h, developed by Park and co-workers in 2012, in which the HTM is the key component for extracting/transporting the photogenerated hole from the perovskite to the back contact metal electrode, effectively minimizing charge-recombination loss at the perovskite/HTM interface and thus achieving good device performance in PSCs. As reported so far, the commercially available Spiro-OMeTAD has been proven to be the most efficient and widely used HTM in most of the highly performing PSCs yielding the record power conversion efficiency (PCE) of PSCs over 25% . However, Spiro-OMeTAD shows low intrinsic hole mobility of about ∼10 –6 cm 2 ·V –1 ·s –1 in its pristine form, resulting in poor photovoltaic performances in devices. Thus, it is extremely important to improve its hole-transfer ability by introducing some chemical additives such as Li-bis­(trifluoromethanesulfonyl)­imide (Li-TFSI) into the Spiro-OMeTAD-based film. It has been reported that inclusion of the additive Li-TFSI can promote the oxidative reaction of pristine Spiro-OMeTAD into Spiro-OMeTAD + in the presence of oxygen and accordingly improve hole mobility by at least 2 orders of magnitude and thus obtain high device performance. , Currently, a great number of new HTMs as alternatives to Spiro-OMeTAD have been extensively developed and applied in PSCs because of tedious synthesis and expensive cost of Spiro-OMeTAD; Li-TFSI was found to be a necessary additive in these HTMs for good device photovoltaic performances. However, the Li-TFSI additive has been identified as the main component heavily responsible for the deterioration of the PSCs performance and stability.…”
mentioning
confidence: 99%
“…In order to address this shortcoming, solid-state hole-transporting material (HTM) 2,2′,7,7′-tetrakis­( N , N -di- p -methoxyphenyl-amine)-9,9′-spirobifluorene (Spiro-OMeTAD) was employed as an alternative to liquid electrolyte to successfully construct the first all solid-state mesoscopic heterojunction PSCs featuring a FTO/c-TiO 2 /m-TiO 2 /perovskite/HTM/Au cell configuration that was stable for 500 h, developed by Park and co-workers in 2012, in which the HTM is the key component for extracting/transporting the photogenerated hole from the perovskite to the back contact metal electrode, effectively minimizing charge-recombination loss at the perovskite/HTM interface and thus achieving good device performance in PSCs. As reported so far, the commercially available Spiro-OMeTAD has been proven to be the most efficient and widely used HTM in most of the highly performing PSCs yielding the record power conversion efficiency (PCE) of PSCs over 25% . However, Spiro-OMeTAD shows low intrinsic hole mobility of about ∼10 –6 cm 2 ·V –1 ·s –1 in its pristine form, resulting in poor photovoltaic performances in devices. Thus, it is extremely important to improve its hole-transfer ability by introducing some chemical additives such as Li-bis­(trifluoromethanesulfonyl)­imide (Li-TFSI) into the Spiro-OMeTAD-based film. It has been reported that inclusion of the additive Li-TFSI can promote the oxidative reaction of pristine Spiro-OMeTAD into Spiro-OMeTAD + in the presence of oxygen and accordingly improve hole mobility by at least 2 orders of magnitude and thus obtain high device performance. , Currently, a great number of new HTMs as alternatives to Spiro-OMeTAD have been extensively developed and applied in PSCs because of tedious synthesis and expensive cost of Spiro-OMeTAD; Li-TFSI was found to be a necessary additive in these HTMs for good device photovoltaic performances. However, the Li-TFSI additive has been identified as the main component heavily responsible for the deterioration of the PSCs performance and stability.…”
mentioning
confidence: 99%
“…5(d), the PVK/SP + W sample degrades at a lower rate than the PVK/SP sample under the operating conditions or a thermal environment, which is attributed to 1T-WS 2 suppressing the movement of some active ions in the hybrid system (e.g., the migration/diffusion of Li ions in spiro-OMeTAD, the precipitation/migration of inorganic/organic ions in the absorber). 39,[41][42][43][44] The comprehensive results show that 1T-WS 2 plays an important role in improving the PV output and stability of b-PSCs. Such findings can drive the rapid development of innovative PV devices in the industry.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, the HOMO energy levels of MT1 and MT2 versus vacuum are calculated to be À5.30 and À5.35 eV, respectively, which are downward shifted relative to their analogues with methoxy as the terminal groups. 47 Notably, the HOMO energy levels of MT1 and MT2 are lower than that of spiro-OMeTAD (À5.12 eV) but still more positive than the valence band of the perovskite (À5.44 eV). 49 Therefore, cascade HOMO level alignment could be expected when the two compounds were utilized as interfacial materials in perovskite solar cell devices (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…[43][44][45] This motivated us to develop semiconducting interfacial materials (SIMs) through functionalizing D-p-D molecular semiconductors. In most cases, the donor units of these molecular semiconductors are methoxy substituted arylamine derivatives such as diphenylamine, 46,47 triphenylamine and carbazole. 48 The terminal methoxy groups play an important role in modulating the energy level and anchoring the material onto the underlying perovskite layer.…”
Section: Introductionmentioning
confidence: 99%